PENGARUH TEKNIK TRI-FOKUS STEVE SNYDER TERHADAP KECEPATAN EFEKTIF MEMBACA SISWA KELAS X SMA SWASTA MUHAMMADDYAH RANTAU PRAPAT TAHUN AJARAN 2018/2019 - Rosmawaty Harahap; Rosdiana Siregar; Ibnu Husaini (Universitas Negeri Medan, 2021)
Abstract Reading is one of the four aspects of language skills. Reading including receptive skills, which serve to absorb the information. The low reading proficiency will greatly affect the effectiveness of students' reading. This paper describes the influence of engineering Steve Snyder Tri-focus on effective speed reading class X SMA Muhammaddyah academic year 2019/2020. This study is quasi-experimental. The research sample is the class X-1 and X-2. The research concludes effective speed reading speed of students by using Tri-Focus on high school students of class X Muhammaddyah Rantau Prapat classified in either category with an average value of 72.72. While in the classroom with hands-on learning techniques belong to the category of fairly 50.3 Keywords: Read fast , kecepatan efektif membaca ( KEM ) , Tri - Focus technique Steve Snyder